Applied Pediatric Integrative Medicine: What We Can Learn from the Ancient Teachings of Sebastian Kneipp in a Kindergarten Setting - Marion Eckert; Melanie Anheyer (MDPI AG, 2018)
Pediatric integrative medicine focuses on the whole child and the environment in which the child grows up during the treatment of a child’s illness. Nowadays, many different treatment modalities are applied even in children, and doctors need to know about them and, ideally, be able to apply different approaches in the process of treating a child themselves. The program Pediatric Integrative Medicine in Residency (PIMR) already provides residents with several tools to provide this kind of service for the child. In our PIMR pilot program in Germany, we chose to diversify our knowledge about treatment and prevention options by visiting a Kneipp-certified kindergarten in Germany. The philosophy of Sebastian Kneipp focuses on five pillars of health, which incorporate aspects of prevention, self-awareness, self-responsibility, and consciousness of health by means of hydrotherapy, herbal medicine, exercise, nutrition, and lifestyle-medicine. These are being taught to the children during the early years they spend in kindergarten, and represent integral parts of integrative medicine. Integration of Kneipp-based health programs within a kindergarten setting can work well and provides an effective means of early prevention education in childhood.